Psychology and Law: A Symbiosis of Two Social Science Oriented Disciplines - Anigbogu, Chinyelu E K (Practicum Psychologia, 2018)
The paper is aimed at highlighting the confluence of law and psychology: interrogating the extent to which psychology could be applied in/through the law court to further the course of justice under the theme ‘Psychology and Law. The three operative concepts here, therefore, are justice, law and psychology. Law and psychology are two separate disciplines, but have much in common. While psychology’s goal is to understand behavior and law’s goal to regulate it, both fields make assumptions about what causes people to act the way they do. It is a known fact that psychologists, world over, engage in research how to improve the legal system.